Multilayer myocardial strain improves the diagnosis of heart failure with preserved ejection fraction. (21st June 2020) - Tanacli, Radu; Hashemi, Djawid; Neye, Marthe; Motzkus, Laura Astrid; Blum, Moritz; Tahirovic, Elvis; Dordevic, Aleksandar; Kraft, Robin; Zamani, Seyedeh Mahsa; Pieske, Burkert; Düngen, Hans‐Dirk; Kelle, Sebastian
Abstract: Aims: The diagnostic and treatment of patients with heart failure with preserved ejection fraction (HFpEF) are both hampered by an incomplete understanding of the pathophysiology of the disease. Novel imaging tools to adequately identify these patients from individuals with a normal cardiac function and respectively patients with HF with reduced EF are warranted. Computing multilayer myocardial strain with feature tracking is a fast and accurate method to assess cardiac deformation. Our purpose was to assess the HFpEF diagnostic ability of multilayer strain parameters and compare their sensitivity and specificity with other established parameters. Methods and results: We included 20 patients with a diagnosis of HFpEF and, respectively, 20 matched controls. We assessed using feature‐tracking cardiac magnetic resonance longitudinal and circumferential myocardial strain at three distinct layers of the myocardium: subendocardial (Endo‐), mid‐myocardial (Myo‐), and subepicardial (Epi‐). Comparatively, we additionally assessed various others clinical, imaging, and biochemical parameters with a putative role in HFpEF diagnostic: left ventricular end‐diastolic volume (LVEDV), left ventricular mass (LVM), interventricular septum (IVS) wall thickness and free wall thickness, left atrial volume and strain, septal and lateral mitral annular early diastolic velocity (e`), E/e´ ratio, and plasma levels of N‐terminal pro‐B‐type natriuretic peptide (NT‐proBNP). Global longitudinal strain (GLS) is significantly impaired at Endo (−20.8 ± 4.0 vs. −23.2 ± 3.4, P  = 0.046), Myo‐ (−18.0 ± 3.0 vs. −21.0 ± 2.5, P  = 0.002), and Epi‐ (−12.2 ± 2.0 vs. −16.2 ± 2.5, P  < 0.001) levels. Compared with any other imaging parameter, an Epi‐GLS lower than 13% shows the highest ability to detect patients with HFpEF [area under the curve (AUC) = 0.90 (0.81–1), P  < 0.001] and in tandem with NT‐proBNP can diagnose with maximal sensibility (93%) and specificity (100%), patients with HFpEF from normal, composed variable [AUC = 0.98 (0.95–1), P  < 0.001]. In a logistic regression model, a composite predictive variable taking into account both GLS Epi and NT‐proBNP values in each individual subject reached a sensitivity of 89% and a specificity of 100% with an AUC of 0.98 (0.95–1), P  < 0.001, to detect HFpEF. Conclusions: Epi‐GLS is a promising new imaging parameter to be considered in the clinical assessment of HFpEF patients. Given its excellent specificity, in tandem with a highly sensitive parameter such as NT‐proBNP, Epi‐GLS holds the potential to greatly improve the current diagnostic algorithms.